2013
DOI: 10.3174/ajnr.a3472
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution MRI of the Intraparotid Facial Nerve Based on a Microsurface Coil and a 3D Reversed Fast Imaging with Steady-State Precession DWI Sequence at 3T

Abstract: BACKGROUND AND PURPOSE: 3D high-resolution MR imaging can provide reliable information for defining the exact relationships between the intraparotid facial nerve and adjacent structures. The purpose of this study was to explore the clinical value of using a surface coil combined with a 3D-PSIF-DWI sequence in intraparotid facial nerve imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…Extracranial imaging of the nerve is not well documented or performed. Chu et al have reported excellent imaging of the extracranial portion of the facial nerve by using high‐resolution MRI based on a micro surface coil; however, these techniques are not readily available at most institutions. When these modalities are refined and in more general use, the findings reported here can be more accurately defined and assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Extracranial imaging of the nerve is not well documented or performed. Chu et al have reported excellent imaging of the extracranial portion of the facial nerve by using high‐resolution MRI based on a micro surface coil; however, these techniques are not readily available at most institutions. When these modalities are refined and in more general use, the findings reported here can be more accurately defined and assessed.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation was the disuse of a surface coil, which could achieve better visualization of the intraparotid facial nerve. 20,21 However, we found that using the surface coil was not feasible in routine clinical practice due to its time-consuming and cumbersome application. Despite the lack of a surface coil, this study still demonstrated good diagnostic performance using a standard, commercially available head and neck coil, and the acquisition time of the 3D-DESS-WE sequence was relatively short, maintaining its feasibility for routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chu et al (42) reported combined use of microsurface coils and a 3D PSIF sequence for high-resolution imaging of the intraparotid facial nerve. These peripheral trunks and branches are best seen on thick-slab sagittal MIP images (Fig 5).…”
Section: Facial Nervementioning
confidence: 99%